Pelatihan Teknik Pembuatan Konten Menarik dan Informatif Untuk Media Sosial Bagi Penggiat Literasi Digital Desa Gladagsari, Boyolali - Dewi, Maya Utami; Nugroho, Aris Sarwo; Kholifah, Siti; Siswanto, Siswanto; Sumaryanto, Sumaryanto; Fitrianto, Yuli; Qosidah, Nanik; Nurmana, Ayyub Hamdanu Budi; Supriadi, Candra; Imaliya, Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
In this increasingly advanced digital era, social media has become the leading platform for many individuals and organizations to convey messages and information to a broad audience. The training activity on interesting and informative content creation techniques for social media for digital literacy activists in Gladagsari Village, Boyolali, aims to equip participants with the knowledge and skills needed to create content that not only attracts attention but also provides high informative value and relevance. Good content is not only able to attract the attention of the audience but is also able to convey messages clearly and increase interaction and engagement. This training was attended by 15 participants and was held in Gondang Village, Ampel District, Boyolali Regency. The training uses theoretical and practical delivery techniques. The training material focuses on creating interesting and innovative content for social media platforms with copywriting techniques. The results of the training showed satisfactory results with an increase in participants' ability to create content on social media with a value of 78%, which is included in the good category.